2008
DOI: 10.1001/archopht.126.6.849
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vision Loss on Costs and Outcomes in Medicare Beneficiaries With Glaucoma

Abstract: To assess the impact of vision loss severity on costs and health outcomes among Medicare beneficiaries with glaucoma. Methods: A retrospective cohort analysis was conducted using Medicare claims. Patients were stratified into 4 categories: no vision loss, moderate vision loss, severe vision loss, and blindness. Outcomes of interest were mean annual medical costs by category, component costs, and frequency of depression, falls and/or accidents, injury, femur fracture, and nursing home placement. Results: Multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 55 publications
0
61
0
2
Order By: Relevance
“…By strengthening emotional brain reactivity in these areas, ambient blue light in the responses of the thalamus (including in the pulvinar) and in the brainstem related to auditory cognitive tasks might promote accurate and contrasting responses to emotional signals, which could ultimately enhance efficient mood regulation processes. In fact, recent reports showed that prolonged darkness or lack of light in rodents induces a depression-like state associated with structural brain changes (46), whereas complete blindness increases depression risk (47). Likewise, long-term changes in ambient light daily profile, such as light therapy, seem to restore normal mood regulation (1,2), and the spectral composition of light changes across the seasons (48).…”
Section: Discussionmentioning
confidence: 99%
“…By strengthening emotional brain reactivity in these areas, ambient blue light in the responses of the thalamus (including in the pulvinar) and in the brainstem related to auditory cognitive tasks might promote accurate and contrasting responses to emotional signals, which could ultimately enhance efficient mood regulation processes. In fact, recent reports showed that prolonged darkness or lack of light in rodents induces a depression-like state associated with structural brain changes (46), whereas complete blindness increases depression risk (47). Likewise, long-term changes in ambient light daily profile, such as light therapy, seem to restore normal mood regulation (1,2), and the spectral composition of light changes across the seasons (48).…”
Section: Discussionmentioning
confidence: 99%
“…As the cost of treating glaucoma increases by 46% after the occurrence of vision loss, 69 delaying disease-related vision loss in POAG is not solely critical to maintain patients' quality of life but also to reduce associated health-economic burdens. Screening for early-stage POAG using saccadic eye movements can potentially complement ongoing endeavors for a timely detection of this debilitating disease.…”
Section: 98mentioning
confidence: 99%
“…Annual eye care-related costs for glaucoma patients with no vision loss were $8157 (2007 US dollars); this increased to $14,237 for moderate to severe vision loss before reaching $18,670 for patients blinded by the disease. 5 A major risk factor for glaucoma is age; however, the only modifiable risk factor -and the sole target for clinical intervention -is elevated intraocular pressure (IOP). 6 First line treatment for glaucoma is the use of topical eye drops containing IOP-lowering drugs.…”
Section: Introductionmentioning
confidence: 99%